Ilian, Ilinca (2013): Julio Cortázar y Robert Musil: consonancias, divergencias y ecos. Madrid: Ediciones Clásicas; 237 pp. - Maja Šabec (Verba Hispanica, 2015)
Ilian, Ilinca (2013): Julio Cortázar y Robert Musil: consonancias, divergencias y ecos. Madrid: Ediciones Clásicas; 237 pp.